Expression of laminin in benign and malignant sclerosing lesions of extrahepatic bile ducts. Issue 9 (September 1989) - Haglund, C; Roberts, P J; Nordling, S
Abstract : The distribution of laminin, a basement membrane glycoprotein, was studied by an immunohistochemical technique in six samples of benign sclerosing lesions of extrahepatic bile ducts and in 11 sclerosing cholangiocarcinomas. The expression of laminin showed that benign glandular structures were surrounded by a mainly intact basement membrane. In sclerosing cholangiocarcinomas laminin was irregularly distributed, and in large areas totally absent. The findings suggest that deposition of basement membrane material is defective. Sclerosing cholangitis may be extremely difficult to distinguish from well differentiated sclerosing cholangiocarcinoma. This sample was small, but the diseases studied were relatively rare. Staining for laminin might be of additional use to surgical pathologists in the differential diagnosis of benign sclerosing lesions and sclerosing cholangiocarcinomas.